Performance Model and the Problems of Packaging Balinese Dance in the New Normal Era - Ida Ayu Trisnawati; Sulistyani Sulistyani (Lekesan: Interdisciplinary Journal of Asia Pacific Arts, 2021)
This study aims to explain the adaptation patterns of dance in the new normal era to maintain the existence of art and prevented Covid-19 terviews, and observations of various art performances in the new normal era. Furthermore, the data were analyzed with interactive analysis and presented critically with analysis assisted by the socio-cultural theory and art. Research results show that Covid-19 has changed various orders of human life, including dance. Dance performances must follow health protocols to prevent the spread of Covid-19, as a result, there is an adaptation from aesthetics to health. This then led to the staging of the Covid-19 model using various preventative equipment such as masks, face shields, keeping your distance, wearing hand slopes, limiting the number of spectators, and virtual performances. All done by the artist to be able to keep performing arts, but also not neglecting the safety of the dancers, musicians, and the audience. Even though it is realized that using various Covid-19 prevention equipment has caused the aesthetic level of art to decrease. Also, artists experience various problems such as discomfort when performing, the problem of uneven technology facilities, the cost of providing expensive equipment, many artists do not have sufficient knowledge of digital art. Even so, artists are still trying to adapt to be accepted by the wider community in the new normal era.